Pengaruh Profitabilitas, Struktur Modal Dan Ukuran Perusahaan Terhadap Nilai Perusahaan Pada Perusahaan Manufaktur - Ni Wayan Novita Kurnia Sari; I Wayan Sudiana; I Putu Deddy Samtika Putra (Hita Akuntansi dan Keuangan, 2022)
In an effort to see the factors that can increase the value of the company, this research was conducted. With the hope of seeing the relationship between profitability, the effect of capital structure, and firm size on increasing firm value, especially the food and beverage sub-sector. The location of the research was carried out on the IDX which took manufacturing companies in the food and beverage sub-sector. The research sample is 58 company data from 2018 - 2020. The data collected will later be processed using the classical assumption test, multiple linear regression analysis techniques, determination test, F test and t test. With the results of research which states that an increase in firm value can occur with an increase in profitability and the company's capital structure. But firm value cannot be affected by firm value.